Vliv náhlých zmēn teploty a tlaku vzduchu na umrtnost v CR - Plavcová, E; Kyselý, J (Epidemiologie, mikrobiologie, imunologie, 2009)
We have developed an algorithm for identifying sudden changes in air pressure and temperature over the Czech Republic. Such events were retrieved from the data covering in 1986-2005 and were matched with the daily numbers of all-cause deaths and deaths due to cardiovascular diseases from the national database, separately for the whole population and that aged 70 years and over. Excess daily mortality was determined by calculating deviations of the observed number of deaths from the expected number of deaths for each day in the respective groups. The relative deviation of the mortality the mean was calculated as the ratio of the excess mortality to the expected number of deaths. We used 3-hour air pressure data from 10 meteorological stations and hourly air temperature data from 9 stations representative of the Czech Republic. Pressure changes were evaluated on time scales of 3, 6 and 12 hours, separately for summer and winter time. Temperature changes were evaluated on a 24-hour time scale, separately for summer and winter season. Events characterized by pressure or temperature changes above the critical threshold and recorded within 24 hours at more than 50% of meteorological stations were retrieved. The critical thresholds were defined separately for each station using quantiles of distributions of air pressure and temperature changes. Relative mortality deviations for days D-2 (2 days before the change) to D+7 (7 days after the change) were averaged over the retrieved events. Statistical significance of the mean relative deviation was tested using the Monte Carlo method. Increased mortality followed large temperature increases and large pressure drops both in summer and winter months. Decreased mortality was observed after large pressure increases and large temperature drops in summer. Mortality variations are usually more pronounced in the population aged 70 years and over, and cardiovascular diseases account for most deaths after sudden temperature changes.
Keywords: Meteorological Concepts; Česká republika; Air Pressure; Temperature; lidé; Mortality; Czech Republic; tlak vzduchu; teplota; meteorologické pojmy; mortalita; Humans